Number of Testicular Cells in Male Mice (Mus musculus L.) Treated with Bali Salak Fruit Extract (Salacca zalacca var. Amboinensis) : Jumlah Sel Testis Mencit Jantan (Mus musculus L.) yang Diberi Ekstrak Buah Salak Bali (Salacca zalacca Var. Amboinensis) - Padmiswari, Anak Agung Istri Mas; Wulansari, Nedya Treesna; Indrayoni, Putu (BIO-EDU: Jurnal Pendidikan Biologi, 2025)
Spermatogenesis is a complex process influenced by various factors, including nutrition and bioactive compounds from natural sources. Salak Bali fruit (Salacca zalacca Var. Amboinensis) is known to contain antioxidant compounds that may support male reproductive health, particularly in enhancing testicular cell count. This study aims to analyze the effect of salak Bali fruit extract on the testicular cell count of male mice (Mus musculus L.). This research employed an experimental design using a Completely Randomized Design (CRD) with 24 healthy male mice divided into four treatment groups. The control group (K) received only distilled water, while the treatment groups were administered salak Bali fruit extract at doses of 200 mg/kg BW (P1), 400 mg/kg BW (P2), and 600 mg/kg BW (P3) for 35 days. Data analysis was conducted using a one-way ANOVA test, followed by a post hoc test if a significant difference was found (p < 0.05). The results indicated that the treatment groups exhibited a higher average testicular cell count compared to the control group. The most optimal increase was observed in the group receiving a 600 mg/kg BW dose (P3). This suggests that the bioactive compounds in salak Bali fruit may play a role in enhancing the spermatogenesis process.